2013
DOI: 10.1007/s00216-013-6851-z
|View full text |Cite
|
Sign up to set email alerts
|

“Do it yourself” reference materials for δ 13C determinations by isotope ratio mass spectrometry

Abstract: A method is described to prepare inexpensive organic reference materials for routine stable isotope work. The method blends isotope-enriched and isotope-depleted materials to match closely international measurement standards. Examples are presented showing how (13)C-enriched and (13)C-depleted glucose were blended to match the isotopic compositions of the international carbon isotope standards, NBS 19 and L-SVEC. Preparation of the blended standards was straightforward, and the prepared solutions proved easy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This can be both time‐consuming and difficult to apply. Producing solutions of simple single chemicals is one approach to ensuring homogeneity 23 . Those solutions could also be freeze‐dried in sufficiently small droplets if a solid form is required 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be both time‐consuming and difficult to apply. Producing solutions of simple single chemicals is one approach to ensuring homogeneity 23 . Those solutions could also be freeze‐dried in sufficiently small droplets if a solid form is required 9 …”
Section: Methodsmentioning
confidence: 99%
“…Producing solutions of simple single chemicals is one approach to ensuring homogeneity. 23 Those solutions could also be freeze-dried in sufficiently small droplets if a solid form is required. 9 For more complex matrices such as biological tissues or soil, material preparation can become laborious.…”
Section: Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…We passed DOC and 13 C-DOC samples through pre-combusted Whatman GF/F filters (Whatman, Inc., Florham Park, NJ, U.S.A. 195%). The mixed standards were prepared from 13 C-labeled urea and urea with a natural isotope abundance by isotope blending (Carter and Fry 2013). The precision of enriched samples was \ 20%.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…When considering links between MA from multiple seizures, 20 comparisons of δ 13 C / δ 15 N compositions were also found to highlight different grouping patterns 21 compared to conventional profiling techniques [13]. 22 Early research demonstrated that batches of MA, manufactured by reductive amination of 1-23 phenylpropan-2-one (aka phenylacetone or P2P), using identical reagents and equipment had 24 markedly different δ 15 N compositions [14]. Further, systematic research into the preparation of 25 MDMA by reductive amination found significant isotopic variation with changing reaction 26 conditions; δ 2 H values were most affected by imine stir time; δ 13 C values were most affected by 27 the overall efficiency (completeness) of the reaction; δ 15 N values were most affected by an excess 28 of methylamine [15].…”
mentioning
confidence: 99%